EngagINg the COmmunity to Reduce Preterm birth via Adherence To an Individualized Prematurity Prevention Plan (INCORPorATe IP3): intervention development and future pilot study design. (12th December 2022) - Wheeler, Sarahn M.; Jackson, Maya; Massengale, Kelley E. C.; Ramey-Collier, Khaila; Østbye, Truls; Corneli, Amy; Bosworth, Hayden B.; Swamy, Geeta K.
Abstract: Objective: Non-Hispanic Black birthing individuals are at increased risk of preterm birth compared to other racial and ethnic groups. In our clinical setting, we offer a tailored package of recommendations to reduce the risk of preterm birth known as an individualized prematurity prevention plan (IP3). Patient-centered, community engaged interventions that address patient-perceived barriers to preterm birth prevention are urgently needed. Materials and methods: We engaged a group of stakeholders to develop a mutli-level (patient-centered and community-involved) intervention that will increase adherence to an individualized prematurity prevention plan (IP3) by addressing barriers identified during our prior qualitative studies. Results: The intervention includes trained doulas from a community-led, Black owned doula group. The doulas will moderate group prenatal social support sessions. In between the group sessions, participants will be encouraged to continue interacting with one another and the doulas using a private Facebook™ group page. We will pilot test the intervention in a cohort of pregnant, self-identified non-Hispanic Black patients with a history of prior preterm birth. Conclusion: We present a novel, patient-centered, community engaged intervention to reduce preterm birth in high-risk non-Hispanic Black birthing individuals. If the intervention is feasible based on the pilot study findings, we anticipate conducting an appropriately powered study to determine whether the intervention achieves our goal of reducing preterm birth.